2010
DOI: 10.1017/s0317167100009641
|View full text |Cite
|
Sign up to set email alerts
|

Admission and Acute Complication Rate for Outpatient Lumbar Microdiscectomy

Abstract: Specialization is generally independently associated with improved outcomes for all types of surgery.1-2 This is primarily attributed to specialized surgeons being more likely to perform higher volumes of select procedures. 1 Degenerative disc disease of the lumbar spine is a prevalent and costly ailment that often requires surgical intervention.3 A significant number of patients have further reoperations [14%] or develop failed back syndrome [8-25%] which is failure to improve satisfactorily following surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Several studies have already been published claiming the feasibility, safety, and favorable clinical outcome after ACDF and posterior lumbar decompression in the outpatient setting. [8][9][10][11][12][13][14][15][16] However, there continues to be a great deal of skepticism regarding outpatient spine surgery, especially in the diagnosis and treatment of early surgical complications such as hematomas. This series of 1449 consecutive outpatient microsurgical spine decompressions, 376 cervical and 1073 lumbar, adds to the growing literature in favor of outpatient spine surgery, in properly selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already been published claiming the feasibility, safety, and favorable clinical outcome after ACDF and posterior lumbar decompression in the outpatient setting. [8][9][10][11][12][13][14][15][16] However, there continues to be a great deal of skepticism regarding outpatient spine surgery, especially in the diagnosis and treatment of early surgical complications such as hematomas. This series of 1449 consecutive outpatient microsurgical spine decompressions, 376 cervical and 1073 lumbar, adds to the growing literature in favor of outpatient spine surgery, in properly selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…15,26,34,71 Thus, the length of hospital stay was not examined due to its limited clinical significance. Although many of the potential benefits to MID, including deceased postoperative pain and faster mobilization, manifest during the initial postoperative period, few studies reported data on these parameters during this time period.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar microdiscectomy, initially performed in the hospi-neurológica número uno realizado en el país y la primera cirugía mayor de tal setting, has become the first major spine surgery to transition into the ambulatory setting. This push to move surgeries from an inpatient setting to ambulatory setting offers faster recovery time and better postoperative outcomes (12)(13)(14). Various studies (6,(12)(13)(14)(15) have stated that performing lumbar microdiscectomy in the outpatient setting can provide satisfactory outcomes but currently there is no study in the literature to the author's knowledge that analyses the incidence and location of surgery for lumbar microdiscectomy in a national sample.…”
Section: Introductionmentioning
confidence: 99%
“…This push to move surgeries from an inpatient setting to ambulatory setting offers faster recovery time and better postoperative outcomes (12)(13)(14). Various studies (6,(12)(13)(14)(15) have stated that performing lumbar microdiscectomy in the outpatient setting can provide satisfactory outcomes but currently there is no study in the literature to the author's knowledge that analyses the incidence and location of surgery for lumbar microdiscectomy in a national sample. The purpose of this study was to report on the incidence of lumbar microdiscectomy in the USA over a recent seven-year period (2007-2014), the associated procedural reimbursement costs associated with the inpatient and the outpatient setting and the demographic distribution of the surgeries.…”
Section: Introductionmentioning
confidence: 99%